Mustafa's Sweet Dreams - Abazoglou, Angelos (Greece, 2012)
In the small Turkish town of Gaziantep, 17-year-old Mustafa wants to become a master in the art of making baklava. Amidst the strict training regimen, Mustafa dreams of a life beyond the confines of the expectations of his friends and family.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films